Determination of the Promoting Role of Oleaster Fruit in Protein Synthesis by SDS-PAGE and Some Biochemical Analysis - Gok, Ozlem; Beyaz, Seda; Baspinar, Serpil; Aslan, Abdullah (Mattioli 1885, 2022)
Background and aim: Oleaster fruit (Elaeagnus angustifolia) have been used in traditional medicine to treat various diseases. In this study, the effect of oleaster fruit extract on oxidative damage in culture of Saccharomyces cerevisiae (S. cerevisiae) caused by copper chloride (CuCl2) was investigated. Methods: In this study, 4 groups were formed. Groups; (i) Control group; (ii) Oleaster Fruit (8%) Group; (iii) CuCl2 (30 mM) Group; (iv) Oleaster Fruit (8%) + CuCl2 (30 mM) Group. S. cerevisiae cultures were grown at 30 °C for 1 hour, 3 hours, 5 hours and 24 hours. Cell growth, lipid peroxidation, MDA (malondialdehyde) analyzes, glutathione (GSH) levels and catalase activities were determined by spectrophotometer. Total protein changes were detected by SDS-PAGE electrophoresis and calculated by the Lowry method. Results: According to the results obtained; oleaster fruit extract added to S. cerevisiae cultures showed cell growth (1, 3, 5 and 24 hours), total protein synthesis (1 hour, 3 hours, 5 hours and 24 hours), GSH levels (24 hours) and catalase activities (24 hours) and decreased the MDA level (24 hours). Conclusions: These results show that the oleaster fruit extract reduces oxidative damage, enhances cell growth and has a protective effect to promote protein synthesis in S. cerevisiae culture. © 2022 Mattioli 1885. All rights reserved.
Keywords: copper chloride; oleaster fruit; protein; Saccharomyces cerevisiae; SDS-PAGE